Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/molecules24112137
|View full text |Cite
|
Sign up to set email alerts
|

The Properties and Tortilla Making of Corn Flour from Enzymatic Wet-Milling

Abstract: Corn flour was prepared by wet-milling with the treatment of neutral protease and the gelatinization, thermal and rheological properties were analyzed. Tortilla was prepared with enzyme treated corn flour (ECF) and additives (xanthan gum and cassava starch) and the properties were analyzed. Compared with dry-milling corn flour (DCF) and wet-milling corn flour (WCF), the ECF had less average particle size (16.74 μm), higher peak viscosity and higher final viscosity of 2997 cP and 3300 cP, respectively. The ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…There were significant differences (p < 0.05) in T o , T p , T f , and ∆H of flours obtained by different nixtamalization methods. The T o (70.23 • C), T p (78.15 • C), and T f (80.17 • C) of TF were similar to values reported by Liu, Yuan, and Wang [66] for dry milling corn flour. On the other hand, the T o (65.19 • C), T p (67.30 • C), and T f (69.28 • C) of CF were significantly lower (p < 0.05) than TF, which can be attributed to the granule size and distribution of starch [69].…”
Section: Physicochemical Properties Of Traditional and Commercial Torsupporting
confidence: 86%
See 1 more Smart Citation
“…There were significant differences (p < 0.05) in T o , T p , T f , and ∆H of flours obtained by different nixtamalization methods. The T o (70.23 • C), T p (78.15 • C), and T f (80.17 • C) of TF were similar to values reported by Liu, Yuan, and Wang [66] for dry milling corn flour. On the other hand, the T o (65.19 • C), T p (67.30 • C), and T f (69.28 • C) of CF were significantly lower (p < 0.05) than TF, which can be attributed to the granule size and distribution of starch [69].…”
Section: Physicochemical Properties Of Traditional and Commercial Torsupporting
confidence: 86%
“…Commercial nixtamalized corn flour showed granules with a regular polygonal shape with no damage and covered with the protein matrix ( Figure 6a). The traditional nixtamalized corn flour exhibited starch granules with a polygonal shape ( Figure 6e); nevertheless, some granules showed cavities (see black circle) and the protein matrix was scarcely noticeable and less rough, which implies a partial solubilization [66]. The morphological modifications were related with starch damage during the nixtamalization process, as has been previously reported [12].…”
Section: Physicochemical Properties Of Traditional and Commercial Torsupporting
confidence: 72%
“…The black rice starch granules (Fig. 2a), as it is known, are small (most have 3–6 µm), often with an invisible hilum, without concentric streaks and with a higher tendency of aggregation (Liu et al ., 2019; Milea et al ., 2020). Instead, the corn starch granules are larger (10–20 µm), with less sharp edges between the facets, and often with visible hilum, stellate, or punctate (Croitoru et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Yolanda and Nandiyanto (2022) provided detailed steps on how to read and measure the diameter of material using SEM. Martelo et al (2021) used SEM to characterize the surface topography of coated paperboard, Khan et al (2022) used SEM to investigate the microstructural changes of wheat flours and doughs, and Liu et al (2019) used SEM for corn flour. Meanwhile, Rosli and Ain (2014) reported that the cross-sectional diameters for brown rice and white rice samples were in the range of 847 to 1000 µm.…”
Section: Introductionmentioning
confidence: 99%